Integrating Rationality and Religiosity In Financial Literacy Education: Strengthening Investment Awareness And Preventing Illegal Online Lending At Tahfiz Al-Qur’an Izzudin Islamic Boarding School - Malinda, Shelfi; Febrianti, Rahma; Yuliani, Yuliani; Shafira Vanessa, Aulia; Efriani, Betharia; Nettiary Kelara, Bulan (International Journal Of Community Service, 2025)
The rapid expansion of financial technology in Indonesia has stimulated a surge of interest in digital investment. However, this progress has not been matched by a proportional improvement in financial literacy, resulting in the increasing prevalence of illegal investment schemes and unregulated online lending practices. Although national data show a sharp rise in the number of investors in 2021, the trend has declined steadily from 2022 to 2025, accompanied by fluctuating growth in illegal financial activities. This phenomenon indicates a critical imbalance between access to digital financial platforms and the ability of individuals to manage the associated risks responsibly. Most existing financial literacy initiatives focus primarily on economic rationality, overlooking the moral and spiritual dimensions that strongly influence decision-making in religious-based educational settings. Addressing this limitation, the present community service program was designed to integrate rational and religious approaches in developing ethical and prudent financial behavior among students of Pesantren Tahfizh Al-Qur’an Izzuddin Palembang. The implementation involved interactive lectures, case-based discussions, and simulations, evaluation through pre-test and post-test assessments to measure participants’ learning progress. The results demonstrated a notable improvement in understanding digital financial risks and awareness of illegal investment practices after the intervention. This initiative underscores the significance of combining rational, educational, and religious perspectives to strengthen financial literacy resilience in the digital era, particularly within faith-based learning environments. The model developed through this program offers a sustainable approach to preventing illegal financial activities while fostering financially literate and ethically conscious youth.